MENINGKATKAN PEMAHAMAN KONSEP PECAHAN MELALUI PENDEKATAN REALISTIC MATHEMATICSEDUCATION (RME) PADA PELAJARAN MATEMATIKA KELAS V DI SDIT YPI “45” BEKASI - Yuyun Komala; Yetti Supriyati; Fathiaty Murtadho (Jurnal Numeracy, 2018)
This study aims to improve understanding of the concept of fractions in mathematics lessons for fifth grade students in SDIT YPI "45" Bekasi through the Realistic Mathematics Education (RME) Approach. The research method that will be carried out is using the action research procedure (Action Research) model of Kemmis and Taggart using a spiral system. In each cycle include planning (planning), action (implementation), observation (observation) and reflection (reflection) stages. action research was conducted in class V with 21 students. This research instrument is in the form of interviews, observation sheets and field notes. The results of observation of student activities in learning cycle I and cycle II obtained an increase with a percentage of 79.27% ​​with enough categories, increasing to 92.15% with very good categories. The percentage of students who completed the pre-cycle stage was 52.38%, the first cycle was 71.4%, and the second cycle increased again to 85.7%. The score percentage of each indicator of concept comprehension ability has increased every cycle, such as understanding comprehension, in the first cycle students who are able to answer correctly are 85%, cycle II increases to 100%. The problem of understanding the interpretation of students in the first cycle that was able to answer correctly by 75% increased in the second cycle to 100%. Whereas for extrapolation understanding questions, in the first cycle students who were able to answer only 25%, the second cycle increased to 50%. The results of the findings data, it can be said that the Realistic Mathematics Education (RME) learning approach can improve understanding of the concept of fractions in mathematics in class V SDIT YPI "45" Bekasi. Abstrak Penelitian ini bertujuan untuk meningkatkan pemahaman konsep pecahan pada pelajaran matematika pada siswa kelas V di SDIT YPI “45” Bekasi melalui Pendekatan Realistic Mathematics Education (RME). Metode penelitian yang akan dilakukan adalah menggunakan prosedur penelitian tindakan (Action Research) model Kemmis dan Taggart dengan menggunakan sistem spiral. Dalam setiap siklus meliputi tahapan planning (perencanaan), action (pelaksanaan), observation (observasi) dan reflection (refleksi). penelitian tindakan dilakukan di kelas V dengan jumlah siswa sebanyak 21 siswa. Instrumen penelitan ini berbentuk wawancara, lembar observasi dan catatan lapangan. Hasil observasi aktivitas siswa pada pembelajaran siklus I dan siklus II memperoleh peningkatan dengan persentase 79,27% dengan kategori cukup, meningkat menjadi 92,15% dengan kategori sangat baik. Persentase siswa yang tuntas pada tahap prasiklus sebesar 52,38%, siklus I menjadi 71,4%, dan siklus II meningkat kembali menjadi 85,7%. Persentase skor tiap indikator kemampuan pemahaman konsep mengalami peningkatan setiap siklusnya seperti soal pemahaman translasi, pada siklus I siswa yang mampu menjawab benar sebesar 85%, siklus II meningkat menjadi 100%. Soal pemahaman interprestasi siswa pada siklus I yang mampu menjawab benar sebesar 75% meningkat pada siklus II menjadi 100%. Sedangkan untuk soal pemahaman ekstrapolasi, pada siklus I siswa yang mampu menjawab hanya 25%, siklus II meningkat menjadi 50%. Hasil data penemuan tersebut, dapat dikatakan bahwa pendekatan pembelajaran Realistic Mathematics Education (RME) dapat meningkatkan pemahaman konsep pecahan pada pelajaran matematika di kelas V SDIT YPI “45” Bekasi. Kata kunci: Realistic Mathematics Education (RME), konsep pecahan, pendekatan